2021
DOI: 10.1002/csc2.20341
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and seed traits of high‐oleic soybean lines containing the DP‐305423‐1 transgene in four backcross populations

Abstract: The DP‐305423‐1 transgene elevates oleic acid concentration and reduces polyunsaturated fatty acids in soybean [Glycine max (L.) Merr.] oil, resulting in increased oxidative stability. The objective of this research was to investigate the effect of the DP‐305423‐1 transgene on agronomic and seed traits using four backcross derived soybean populations to provide further understanding of the transgene's influence across varying genetic backgrounds and environments. An equal number of high‐oleic, low‐linolenic (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Breeding for elevated oil concentration in high-oleic soybean germplasm with the DP-305423-1 transgene is an important target. It has been demonstrated that high-oleic progeny have lower oil concentration than full-sib normal oleic progeny (Brace et al, 2011;Hemingway et al, 2020;Spear et al, 2012), and it is conceivable that increasing oil concentration may have a positive impact on the commercial production of high-oleic cultivars. With more oil extracted from a unit of grain, oil processors will have lower costs per unit of oil and higher financial returns resulting in greater financial incentives for soybean producers to grow a higholeic cultivar.…”
Section: Crop Sciencementioning
confidence: 99%
“…Breeding for elevated oil concentration in high-oleic soybean germplasm with the DP-305423-1 transgene is an important target. It has been demonstrated that high-oleic progeny have lower oil concentration than full-sib normal oleic progeny (Brace et al, 2011;Hemingway et al, 2020;Spear et al, 2012), and it is conceivable that increasing oil concentration may have a positive impact on the commercial production of high-oleic cultivars. With more oil extracted from a unit of grain, oil processors will have lower costs per unit of oil and higher financial returns resulting in greater financial incentives for soybean producers to grow a higholeic cultivar.…”
Section: Crop Sciencementioning
confidence: 99%